1990
DOI: 10.1088/0029-5515/30/1/001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of the dynamics of pellet ablation on the Texas Experimental Tokamak (TEXT)

Abstract: The toroidally aligned filaments which are commonly observed to be formed by the ablation of a hydrogen fuelling pellet have been studied in TEXT. The ablatant forms the first distinguishable filament near a critical radius, which appears to be that of the q=2 surface. The positions of the other filaments can be predicted from the ballistic motion of the pellet and a simple time dependent model for pellet ablation. These experimental results indicate that a time dependent model may be required as a refinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
41
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 14 publications
(33 reference statements)
15
41
0
Order By: Relevance
“…The shift is likely associated with the position of the pellet relative to the plasmoid boundaries in the moment of triggering the CCD camera. Analogous conclusion can be arrived at on the basis of the photographic images of Durst et al [29] in which bulging of the plasmoid boundary in the direction of pellet motion is visible and is possibly caused by the approaching pellet. The time resolution used by Durst (exposure times under 1 μs) is finer than the one used for Fig.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The shift is likely associated with the position of the pellet relative to the plasmoid boundaries in the moment of triggering the CCD camera. Analogous conclusion can be arrived at on the basis of the photographic images of Durst et al [29] in which bulging of the plasmoid boundary in the direction of pellet motion is visible and is possibly caused by the approaching pellet. The time resolution used by Durst (exposure times under 1 μs) is finer than the one used for Fig.…”
supporting
confidence: 63%
“…Here D 2 pellets were injected into deuterium plasmas. (Analogous pictures were presented already by Durst et al [29] and others; see Section 2.1 of the review paper by Milora et al [30]). …”
mentioning
confidence: 84%
“…In order to extrapolate a fueling scenario into a future fusion reactor, therefore, it is important to understand the dynamics of a high density plasmoid which is composed of pellet ablated material. The initial stage of the plasmoid movement has been observed using a two-dimensional framing camera in TEXT [10], while the author did not refer to the possibility of ∇B induced drift because there had been no such notion at that time. The dynamics of the plasmoid have been observed directly by use of a one-dimensional fiber optics array in RTP and ASDEX-upgrade [11,12], and the rapid transport of the pellet plasmoid toward magnetically low field side has been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Already the early experiments [17,18] showed that the pellet is surrounded by a cigar shaped cloud which is elongated along the field lines, thus L.L. Lengyel and his co-workers [19,20] were focusing on understanding this observation.…”
Section: Introductionmentioning
confidence: 99%